Peran Komisaris Independen, Ukuran Perusahaan, Kinerja Keuangan dan Leverage Terhadap Usaha Penghindaran Pajak - Kusufiyah, Yunita Valentina; Anggraini, Dina (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
Tax is the biggest contributor in state income, so the process of collecting taxes made by the state becomes very important. This study aims to empirically examine the influence of Independent Commissioners, Company Size, Return On Asset and Debt to Equity Ratio on tax avoidance. This research was conducted on the Indonesia Stock Exchange with the manufacturing sector during 2013-2017. The population in this study were 41 companies with the number of observations 205 obtained using the purposive sampling method. This study uses multiple linear regression data analysis techniques with the results of the study show that independent commissioners and Debt to Equity Ratio do not have a significant effect on tax avoidance practices, while company size and Return On Asset have a negative and significant effect on tax avoidance practices. Keywords : Independent Commissioner, Size, Return On Asset, Debt to Equity Ratio, Tax Avoidance